In Vitro Evaluation and Post-thawing Activation of Najdi, Arabi (Najdi × arabi) Rams Spermatozoa Using Amino Acids and Pentoixfilline Added to Tris Extender - Bushra F. Hassan (Journal of Global Pharma Technology, 2020)
This study was done on pooled semen ejaculates of three groups of rams, Arabi, Najdi and their crosses collected by artificial vagina, semen was evaluated before dilution and after thawing from freezing for one month. Dilution of ram’s semen was done by Tris extender as a standard diluents and its semen parameters was evaluated compared with parameter of extenders after addition of glycine and cysteine amino acids. Then all spermatozoa of all diluents were in vitro activated using CO2 incubator for one hour after addition of pentoxiphilline. Also a new seminal diluents was used which is 5% of beet pulp juice of pH 7. Results revealed that dilution with extender having amino acids have significantly better results than Tris standard extender. Also in vitro activation after addition of pentoxifilline gave same results. It is obvious that glycin extender had the better results followed by cysteine extender then Tris standered extender and lastly the extender of beet pulp juice. Keywords: Extender, Rams spermatozoa, Amino acid, Beet pulp.